Language as a part of the culture and civilization of the peoples of the world Human origin language, evolution, and theories - Feyzolaslam, Jehad (Arab Journal for Sciences and Research Publishing, 2022)
There is no doubt that linguistic studies have expanded in recent times, and have become at the present time the focus of attention of researchers and those interested in language, and studies have increased in this field, everyone has worked on his like in it, but some research still draws attention; because either he has not matured yet, Or because he did not convince the minds of others mentally, scientifically, literaryly or linguistically, how did humans speak the language? when? where? Therefore, the science of linguistics appeared to discuss matters and answer what falters in the astonished and hesitates in ideas. Some researchers have been exposed to this important issue, and by that I mean the emergence, development and diversity of the language, including the Arabic language, and some of them discussed linguistic theories, ancient and modern. But there is still a lot of mystery and ambiguity surrounding the issue of language, and theories in this field are still not mature, and many questions are stuck in our minds, including how did the language begin? How did you grow up? How did you develop? What are the closest theories to reality? Is it possible to know the truth of language? What is the link between language and human culture and civilization? What is the measure of urbanization? These and other questions the researcher tried to address to reach some results, and the goal is to raise interest in the language as part of the cultures and civilizations of the peoples of the world.